The lottery contest is a best-response potential game - Christian Ewerhart (University of Zurich, Department of Economics, 2017)
It is shown that the n-player lottery contest admits a best-response potential (Voorneveld, 2000, Economics Letters). This is true also when the contest technology reflects the possibility of a draw. The result implies, in particular, the existence of a nontrivial example of a strictly competitive game that is best-response equivalent to a game with identical payoff functions.
Keywords: C62; C72; D72; 330; Potential games; Tullock contest; best-response equivalence; zero-sum games